Smart modern hydroponic product / Imran Hakimi Azman - Azman, Imran Hakimi (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
Creating environmentally friendly agriculture is an impediment to our country's economy. Our nation's reliance on imported food is excessive. As a result, the problem can be solved by using hydroponic products, which have the ability to grow crops. This hydroponic technology is designed primarily for indoor use. This device is both space-saving and inexpensive to operate. It also contains information and guidelines on hydroponics as well as instructions to use the product. Given its straightforward design, this product is excellent for use inside the home for modern applications. The main use of this item is not only to care for plants, but it may also improve the ambiance of a space since users can use it as a decorative object. A survey of 30 participants was done using questionnaires, followed by an observation at an urban agriculture site. As a result, the definitive design for educational hydroponics has been completed.